2016
DOI: 10.1177/0165025416673474
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of romantic pathways during emerging adulthood and their developmental antecedents

Abstract: The present study examined patterns of romantic pathways in 100 Israeli emerging adults (54 males) who were followed from age 22 to 29 years. Analyses of interviews at age 29 yielded four distinctive romantic pathways differing in stability and ability to learn from romantic experiences: Sporadic, Lengthy Relationships but Absence of Experiential Learning, Moving from Casual to Steady Involvements, and Steady Relationships. Low efficacy, immature dependency, and level of maternal support measured 7 years earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
1
20
0
3
Order By: Relevance
“…They had difficulties coping with their hurt feelings and moving into new relationships. However, among other emerging adults, a romantic breakup served as a learning experience for future relationships (Shulman, Seiffge-Krenke, Scharf, Bezalel-Boiangiu, & Tregubenko, 2016; Tuval-Mashiach, Hanson, & Shulman, 2014). Given that for some individuals breakup distress subsides, while for others it might persist, the major aim of the current study is to examine the personal characteristics that are associated with greater breakup distress during early emerging adulthood and to learn about the consequences of breakup distress on a current relationship.…”
Section: Introductionmentioning
confidence: 99%
“…They had difficulties coping with their hurt feelings and moving into new relationships. However, among other emerging adults, a romantic breakup served as a learning experience for future relationships (Shulman, Seiffge-Krenke, Scharf, Bezalel-Boiangiu, & Tregubenko, 2016; Tuval-Mashiach, Hanson, & Shulman, 2014). Given that for some individuals breakup distress subsides, while for others it might persist, the major aim of the current study is to examine the personal characteristics that are associated with greater breakup distress during early emerging adulthood and to learn about the consequences of breakup distress on a current relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Viele junge Erwachsene in Deutschland, aber auch in anderen westlichen Industrieländern gehen gegenwärtig unverbindliche sexuelle Begegnungen ein, die sich nach kurzer Zeit auflösen [10]. Es handelt sich um unterschiedliche Muster sexueller Aktivitäten, die von One-Night-Stands und "Sex with the Ex" bis zu gelegentlichen sexuellen Aktivitäten mit Freunden ("Freundschaft + ") reichen können.…”
Section: Angst Vor Intimität? Unverbindliche Sexuelle Beziehungenunclassified
“…Im Längsschnitt kann man verfolgen, dass unverbindliche Sexualbeziehungen bei Männern allmählich in diese verschiedenen Muster überführt werden; es bleibt ein etwas höherer Anteil von Männern mit weiterhin unverbindlichen Beziehungen und distanzierten Formen, was durch die berufliche Mobilität mitbegünstigt wird [10].…”
Section: Fallbeispiel: Herr Bunclassified
“…In sum, previous research has shown that young people's perceptions of good family support influence the establishment of healthy romantic relationships, both in adolescence [31] and in emerging adulthood [24, 27, 32]. Furthermore, parental warmth is also associated with positive romantic relationships during both adolescence [3335] and emerging adulthood [25].…”
Section: Introductionmentioning
confidence: 95%